English learning in transition: Online education during COVID-19 and its post-pandemic impact - Sajib, Md. Nasim Fardose; Vhabna, Fatimatuj (American Journal of STEM Education, 2026)
The COVID-19 pandemic brought a profound shift in the educational landscape, especially in English as a Foreign Language (EFL) setting, as institutions rapidly transitioned from traditional classrooms to online learning environments. The development of the pandemic has induced several implications that necessitate an urgent evaluation of EFL learning strategies, technological adoption, and learner attitudes in the post-COVID era. The implicated impacts from the perspective of the Bangladeshi Tertiary EFL learners are explored in this study. Using a descriptive research design, this study collected quantitative data from a diverse group of 138 tertiary-level EFL students across 13 universities in Bangladesh. Participants were selected through convenience sampling and completed a validated and reliable 4-point Likert scale questionnaire. The data were analyzed using SPSS version 25.0, with a focus on key variables related to learning modalities, technological reliance, and EFL materials and curriculum. The findings reveal significant shifts in EFL learning dynamics, highlighting learners’ positivity on blended learning models over traditional classroom settings. Students reported greater autonomy in learning, enhanced technological affiliation, and an increased reliance on digital resources and communication tools. The identified effects suggest a need for stakeholders—educators, curriculum designers, and policymakers—to consider these evolving preferences and competencies when designing future EFL programs.